Komunikasi Pembangunan Pemerintah melalui BLKK untuk Human Capacity Development - Ihwan Huda Al Mujib; Julien Arief Wicaksono; Nur Afni Rachman; Muhammad Endy Fadlullah (Jurnal Nomosleca, 2022)
Every community empowerment program by the government is expected to give a positive effect and outcome, not only for the community who received it, but also for people who live surround it. Indonesian Ministry of Manpower held many programs trying to empower the community to be better and more productive. One of the programs is Balai Latihan Kerja Komunitas (Vocational and Education Training Center for Community) or known as BLK-K. Pondok Pesantren Annuriyyah is one of the communities which is received this empowerment through BLK-K program. This article elaborates in detail about the “growing-up” process BLK-K in Pondok Pesantren Annuriyyah. By employing qualitative research method, focusing on ethnographic technique, the writers give a concise elaboration in every step passed by the subject being observed. This elaboration is started by the history of establishing, the initiating of empowerment program, till the effect acquired by the community. The elaboration is analyzed using empowerment and development theory. The result shows that the empowerment program, BLK-K, in Pondok Pesantren Annuriyyah, which is focused on welding training, is categorized as a successfully empowerment program that can encourage the community to be an entrepreneur and profitable community.Keywords: Empowerment, BLK-K, Pondok Pesantren